Pengaruh Career Development dan Program Kerja Terhadap Kinerja Karyawan pada Bank Syariah PT. BPRS Puduarta Insani Tembung - Suci Puspita Sari; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of service quality and donation The aim of this research is to find out how work programs and career development influence the performance of Bank Syariah PT employees. BPRS Puduarta Insani Tembung, either in part or all at once. This learning method is associative. The sample taken was 19 people representing the entire workforce. In this research, a questionnaire was used to collect data. The SPSS (Statistical Package for Social Sciences) program version 29.00 was used to process research data. The Career Development Variable at PT BPRS Puduarta Insani Tembung Sharia Bank has quite a large influence on employee performance even though it is only partial. The performance of Bank Syariah PT employees is significantly influenced by the Work Program variable and is partially significant. BPRS Insani Tembung Puduarta. Simultaneously, the Career Development and Work Program variables have a significant effect on employee performance at the Sharia Bank PT. BPRS Puduarta Insani Tembung.